Clinical features of narcolepsy in children vaccinated with AS03 adjuvanted pandemic A/H1N1 2009 influenza vaccine in England. (10th July 2014) - Winstone, Anne Marie; Stellitano, Lesley; Verity, Christopher; Andrews, Nick; Miller, Elizabeth; Stowe, Julia; Shneerson, John
<x xml:space="preserve">Abstract</x> Aim The aim of this study was to investigate whether children in England with narcolepsy who received the ASO3 adjuvanted pandemic A/H1N1 2009 influenza vaccine (Pandemrix) differed clinically from unvaccinated patients. Method A retrospective review was conducted in children with narcolepsy diagnosed by sleep centres and paediatric neurologists in 16 English hospitals. The inclusion criteria were patient age 4 to 18 years, onset of narcolepsy after January 2008, and diagnosis by the time of the key data‐gathering visit in 2011. Clinical data came from hospital notes and general practitioner questionnaires. An expert panel validated the diagnoses. Results Seventy‐five patients with narcolepsy were identified (43 males, 32 females; mean age at onset 10y 4mo, range 3–18y). Of these patients, 11 received the Pandemrix vaccine before narcolepsy onset. On first presentation, there were more frequent reports of cataplexy, among other features, in vaccinated than in unvaccinated patients (82% vs 55%), but only excessive weight gain (55% vs 20%) was significantly more frequent (p=0.03). Facial hypotonia (p=0.03) and tongue protrusion (p=0.01) were eventually seen more frequently in vaccinated children. When considering patients diagnosed within a year of onset, vaccinated children were not diagnosed more rapidly than unvaccinated children. Interpretation Some symptoms and signs of narcolepsy were more frequently reported in Pandemrix–vaccinated patients. There was no evidence of the more rapid diagnosis in vaccinated patients that has been reported in Finland and Sweden.